RGDSP-functionalized peptide hydrogel stimulates growth factor secretion via integrin αv/PI3K/AKT axis for improved wound healing by human amniotic mesenchymal stem cells - Wei, Wei; Huang, Lei; Chen, Luoying; He, Huanhuan; Liu, Yanfei; Feng, Yuan; Lin, Fengqin; Chen, Hui; He, Qing; Zhao, Junhong; Li, Haihong (Frontiers in Bioengineering and Biotechnology, 2024)
The wound healing process involves communication among growth factors, cytokines, signaling pathways, and cells in the extracellular matrix, with growth factors acting as key regulators. Although stem cells can promote wound healing by secreting diverse growth factors, their therapeutic potential is hindered by poor survival and engraftment. Mimicking the stem cell-matrix interactions can improve stem cell survival, regulate their fate, and even enhance their paracrine effects. This study investigated the use of composite RGDmix hydrogel, which can support the survival and proliferation of human amniotic mesenchymal stem cells (hAMSCs), and effectively increase the expression of various growth factors, thereby promoting wound re-epithelialization, angiogenesis, and epidermal maturation. At last, the specific role of integrin αv and PI3K/AKT signaling pathways in the secretion of growth factors were examined by silencing them in vitro and in vivo. Results suggested that the RGDmix hydrogel improved the secretion of growth factors by hAMSCs through the RGDSP/integrin αv/PI3K/AKT axis, thereby enhancing the therapeutic effect in wound healing.